2002
DOI: 10.1152/ajpheart.01013.2001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological preconditioning with resveratrol: an insight with iNOS knockout mice

Abstract: Resveratrol, a natural antioxidant and polyphenol found in grapes and wine, has been found to pharmacologically precondition the heart through the upregulation of nitric oxide (NO). To gain further insight of the role of NO in resveratrol preconditioning, mouse hearts devoid of any copies of inhibitory NO synthase (iNOS) (iNOS knockout) and corresponding wild-type hearts were perfused with 10 microM resveratrol for 15 min followed by 25 min of ischemia and 2 h of reperfusion. Control experiments were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(96 citation statements)
references
References 30 publications
(33 reference statements)
4
91
0
1
Order By: Relevance
“…For instance, iNOS has been suggested to contribute to burn injury-induced muscle apoptosis and atrophy leading to p53 activation and upregulation (Sugita et al, 2012). iNOS inhibition genetically and/or pharmacologically, indeed, results in the reduction of the ongoing apoptosis (Heneka et al, 1999;Imamura et al, 2002;Miyazawa et al, 2003;Kiang et al, 2008). Thus, it can be concluded that p53 overexpression in the gastrocnemius muscle might be resulting from the increased iNOS expression shown in our previous study (Erekat et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, iNOS has been suggested to contribute to burn injury-induced muscle apoptosis and atrophy leading to p53 activation and upregulation (Sugita et al, 2012). iNOS inhibition genetically and/or pharmacologically, indeed, results in the reduction of the ongoing apoptosis (Heneka et al, 1999;Imamura et al, 2002;Miyazawa et al, 2003;Kiang et al, 2008). Thus, it can be concluded that p53 overexpression in the gastrocnemius muscle might be resulting from the increased iNOS expression shown in our previous study (Erekat et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effect of resveratrol on coronary artery disease may be due to its ability to retard the progression of early atherosclerotic lesions. Our previous reports demonstrated significant reduction in oxidative stress and upregulation of inducible nitric oxide synthase (iNOS) mRNA expression leading to the reduction of cardiomyocyte apoptosis by resveratrol [7]. Recent report from our laboratory has also documented the cardioprotective effect of resveratrol in vivo as well as in vitro which operates through the increased induction of thioredoxin (Trx-1), heme oxygenase (HO-1) and vascular endothelial growth factor (VEGF).…”
Section: Introductionmentioning
confidence: 93%
“…37,38 Moreover, in iNOS knockout mice, the antoxidant resveratrol had no protective effects on attenuating cardiac injury, though it protected against cardiac damage in wild-type mice, supporting a protective role of iNOS-related NO as an antioxidant. 39 NO formation through increased NOS activity should be an important protective mechanism during kallistatin treatment after MI injury.…”
Section: Cardioprotection By Kallistatin Via Antioxidation L Gao Et Almentioning
confidence: 99%